2016
DOI: 10.2147/jmdh.s93680
|View full text |Cite
|
Sign up to set email alerts
|

The role of the multidisciplinary health care team in the management of patients with Marfan syndrome

Abstract: Marfan syndrome (MFS) is a rare, severe, chronic, life-threatening disease with multiorgan involvement that requires optimal multidisciplinary care to normalize both prognosis and quality of life. In this article, each key team member of all the medical disciplines of a multidisciplinary health care team at the Hamburg Marfan center gives a personal account of his or her contribution in the management of patients with MFS. The authors show how, with the support of health care managers, key team members organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 91 publications
0
40
0
4
Order By: Relevance
“…We speculate that the latter group might not yet suffer from severe cardiovascular symptoms or findings. However, annual examination of the cardiologic status has been recommended as a minimum from the time of diagnosis for all these groups (Byers et al, ; Loeys & Dietz, ; von Kodolitsch et al, ). Our findings also indicate that acute or prophylactic cardiac surgeries are common in LDS, and previous studies have found that prophylactic aortic root surgery is safe and durable (Byers et al, ; Krohg‐Sorensen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the latter group might not yet suffer from severe cardiovascular symptoms or findings. However, annual examination of the cardiologic status has been recommended as a minimum from the time of diagnosis for all these groups (Byers et al, ; Loeys & Dietz, ; von Kodolitsch et al, ). Our findings also indicate that acute or prophylactic cardiac surgeries are common in LDS, and previous studies have found that prophylactic aortic root surgery is safe and durable (Byers et al, ; Krohg‐Sorensen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This means more individuals will be diagnosed early in life, often without any or with few clinical symptoms. Interdisciplinary medical follow‐up programs are highly recommended, and many patients need specialized aortic surgical treatment prophylactic or acute events (Hiratzka et al, ; Milewicz & Regalado, ; Pepin, Murray, & Byers, ; von Kodolitsch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However sparse studies and case reports emphasize the need for psychosocial support of affected persons [35]. All authors agree on the crucial value of a multidisciplinary approach to rehabilitation for MFS [2, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a central physician/ caregiver, aware of the many possible features should coordinate the care and relay to appropriate specialists whenever needed. The important role of multidisciplinary teams in the management and treatment of Marfan syndrome has been described previously [381].…”
Section: How Can We Keep In Touch With Changes Of Marfan Syndrome?mentioning
confidence: 99%